EDUKASI DALAM MENCEGAH TINDAKAN DI LINGKUNGAN SEKOLAH MELALUI BIMBINGAN KLASIKAL DI MTS SWASTA DARUL ARAFAH KECAMATAN BABALAN, KELURAHAN BRANDAN TIMUR - Ali Daud Hasibuan; Adinda Alvina Wahyuni; Ahmad Yasri; Ayu Rahmawati Siregar; Miftah Suhaila Prayetno; Rizky Abdillah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The aim of this research is to provide education in preventing bullying in the school environment at Darul Arafah Private MTs, Babalan District, East Brandan Village. In this research, the counseling method uses participatory methods, lectures and education through classical guidance. The results obtained from this activity are an increase in students' understanding of the definition, impact, causal factors, how to deal with bullying and punishment for perpetrators of bullying. Previously, they had not received education about actions to prevent bullying.